2022
DOI: 10.1186/s12883-022-03041-1
|View full text |Cite
|
Sign up to set email alerts
|

Real-world evidence of galcanezumab for migraine treatment in Japan: a retrospective analysis

Abstract: Objective To evaluate the efficacy and safety of galcanezumab in patients with migraine in a real-world setting in Japan. Background Galcanezumab is the first anti-calcitonin gene-related peptide monoclonal antibody approved in Japan. To the best of our knowledge, no real-world studies on galcanezumab have been published in any international journal from Japan. Methods We retrospectively examined patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
2
12
0
1
Order By: Relevance
“…Iannone et al reported lower rates of treatment continuation at 12 months compared with our cohort 19. The reported adverse event rate varies in the literature between 19.5% and 73.3%,2 13 20 with similar reported events.…”
Section: Discussionsupporting
confidence: 61%
“…Iannone et al reported lower rates of treatment continuation at 12 months compared with our cohort 19. The reported adverse event rate varies in the literature between 19.5% and 73.3%,2 13 20 with similar reported events.…”
Section: Discussionsupporting
confidence: 61%
“…Patients completed the Generalized Anxiety Disorder-7 (GAD-7) questionnaire [27,28] and Patient Health Questionnaire-9 (PHQ-9) [29] upon CGRPmAb administration to determine the extent of anxiety and depression, respectively. We also collected patient migraine-preventive drug data, including failures of preventative drugs (lomerizine, propranolol, valproate, amitriptyline, or topiramate) before CGRPmAb treatment and response frequency to triptan (0, 1, 2, 3 out of three uses) [10].…”
Section: Research Itemsmentioning
confidence: 99%
“…Previous reports on clinical trials and real-world research show that CGRPmAbs produce substantially better outcomes than other treatments, without causing severe adverse effects [3][4][5][6][7][8][9]. However, CGRPmAbs also have disadvantages; they are more expensive, cause minor adverse effects such as injection site reactions and constipation, and are ineffective in some patients [10]. Currently, in Japan, CGRPmAbs (galcanezumab, fremanezumab, and erenumab) can be used for patients with ≥ 4 migraine days per month and for those who have experienced treatment ineffectiveness/intolerance, or have strong concerns about side effects, with at least one traditional migraine-preventive drug (i.e., lomerizine, propranolol, valproate) [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the reported median number of previous medication failures in study cohorts ranged from 4 to 7, representing a therapy-resistant or difficult-to-treat subset of migraine patients. Within this population, there was a small but consistent negative association between the number of previous CM: chronic migraine [47,48,50,[53][54][55][56][57][58][59][61][62][63]65,66,68,69,74,75,78].…”
Section: Previous Preventive Treatmentsmentioning
confidence: 65%